Care of the Child's Voice: A Pediatric Otolaryngologist's Perspective - Smith, Marshall E. (Seminars in Speech and Language, 2013)
Children with voice problems are encountered by speech-language pathologists working in schools but not with sufficient frequency to yield a great experience in managing them. Their evaluation and treatment now are best handled by a team of specialists in pediatric otolaryngology and speech-language pathology with expertise in voice and resonance disorders. The voice team uses a variety of assessment tools, including perceptual, parent- and patient-based, instrumental, and imaging measures. The most important component of the diagnostic assessment is laryngoscopy in the awake child, to visualize the vocal folds while the child phonates. This review covers the pediatric otolaryngologist's approach to dysphonia in children. The common causes of dysphonia are reviewed, including vocal nodules and other lesions, reflux laryngitis, laryngeal paralysis, congenital glottic webs, laryngeal papillomatosis, functional voice disorders, and velopharyngeal incompetence. Current treatment options are continually being modified. These are discussed by highlighting recently published research.
Keywords: Pediatric voice; dysphonia; voice clinic